1999
DOI: 10.1592/phco.19.9.708.31544
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir Concentrations and Antiviral Effect

Abstract: Indinavir plasma concentrations were highly variable among patients receiving the same dosage. Patients with an undetectable plasma HIV RNA level who were protease inhibitor naive had statistically higher indinavir concentrations and slower oral clearance than the group with detectable HIV RNA. Relationships between indinavir concentrations and anti-HIV effect provide a basis for quantifying the pharmacologic contribution to the heterogeneity in therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 17 publications
5
96
1
Order By: Relevance
“…In the placebo group (indinavir 800 mg alone), indinavir pharmacokinetics varied significantly but was consistent with previously reported pharmacokinetic data. 1 Indinavir's AUC values in our study ranged from 13.7 to 68.7 mg · hr/L and C max values ranged from 7,000 to 25,900 ng/mL. However, these values were similar to or slightly higher than the indinavir AUC values reported under steady-state conditions.…”
Section: Discussioncontrasting
confidence: 56%
“…In the placebo group (indinavir 800 mg alone), indinavir pharmacokinetics varied significantly but was consistent with previously reported pharmacokinetic data. 1 Indinavir's AUC values in our study ranged from 13.7 to 68.7 mg · hr/L and C max values ranged from 7,000 to 25,900 ng/mL. However, these values were similar to or slightly higher than the indinavir AUC values reported under steady-state conditions.…”
Section: Discussioncontrasting
confidence: 56%
“…The impact of low plasma C min on clinical effectiveness of PI-containing regimens is uncertain, although a correlation has been observed between viral load after 12 weeks of therapy and C min . 22 It was observed that children who were Ͼ25 kg and treated TID (with or without NVP) had mean C min values exceeding adult values, although 8 of 30 patients (27%) did not have trough values Ͼ1000 g/L.…”
Section: Discussionmentioning
confidence: 95%
“…The long-term success of ARV treatment depends upon maintaining inhibitory concentrations of active drug at the site of HIV replication sufficient to suppress viral replication. Reduced serum levels of ARV drugs correlate with treatment failure and the development of ARV drug resistance [39][40][41][42]. High serum levels of ARV drugs have been shown to correspond with an increased incidence of [26][27][28] Some patients were issued with warnings for more than one adverse effect or interaction.…”
Section: Discussionmentioning
confidence: 99%